2010
DOI: 10.1088/0953-4075/43/11/115502
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a stored Zeeman coherence grating in an external magnetic field

Abstract: We investigate the evolution of a Zeeman coherence grating induced in a cold atomic cesium sample in the presence of an external magnetic field. The gratings are created in a three-beam light storage configuration using two quasi-collinear writing laser pulses and reading with a counterpropagating pulse after a variable time delay. The phase conjugated pulse arising from the atomic sample is monitored. Collapses and revivals of the retrieved pulse are observed for different polarizations of the laser beams and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 28 publications
(38 reference statements)
0
23
0
4
Order By: Relevance
“…Continuing interest in these phenomena is related not so much to the phenomena themselves, but rather their applications -lasing without inversion [1], laser cooling [2] and stored light [3]. If the system under consideration is not in the CPT state, the polarization characteristics of its radiation can be used for the diagnostics of the anisotropy of the processes occurring in that system.…”
Section: Introductionmentioning
confidence: 99%
“…Continuing interest in these phenomena is related not so much to the phenomena themselves, but rather their applications -lasing without inversion [1], laser cooling [2] and stored light [3]. If the system under consideration is not in the CPT state, the polarization characteristics of its radiation can be used for the diagnostics of the anisotropy of the processes occurring in that system.…”
Section: Introductionmentioning
confidence: 99%
“…Several applications have been proposed and demonstrated experimentally for such atomic gratings: all-optical switching and routing [1], tunable photonic band gaps [2], light storage [3,4], and beam splitting and fanning [5], among others. Many of the different schemes that have been proposed for creating an atomic grating use electromagnetically induced transparency (EIT) [6].…”
Section: Introductionmentioning
confidence: 99%
“…EIG initially was proposed in a Λ-type threelevel atomic system [1], then experimentally demonstrated in cold and hot atomic media [2][3][4]. The great attention to EIG is due to its potential applications in significant fields such as all-optical switching and routing [2], probing material optical properties [4], atomic/molecular velocimetry [5], light storage [6,7], optical bistability realization [8], beam splitting and fanning [9], shaping a biphoton spectrum [10], developing novel photonic devices in semiconductor QW systems [11], and controlling multi-wave mixing signals via photonic band gap of electromagnetically induced absorption grating in atomic media [12]. It is shown that the intensity of higher-order diffractions could be enhanced in a three-level ladder type system [13].…”
Section: Introductionmentioning
confidence: 99%